Determinants of Quality of Life According to Cognitive Status in Parkinson’s Disease - Fan, Yun; Liang, Xiaoniu; Han, Linlin; Shen, Yan; Shen, Bo; Chen, Chen; Sun, Yimin; Wang, Jian; Tang, Yilin (Frontiers in Aging Neuroscience, 2020)
Background: Quality of life (QoL) was worse in Parkinson's disease patients with mild cognitive impairment (PD-MCI) or dementia (PDD) than PD patients with normal cognition (PD-NC). The aim of this study was to investigate and compare the potential heterogeneous determinants of QoL in PD patients with different cognitive statuses. Methods: We recruited 600 PD patients, including 185 PD-NC patients, 336 PD-MCI patients and 79 PDD patients, in this cross-sectional study. All patients completed the QoL assessment by the 39-item Parkinson's Disease Questionnaire (PDQ-39), as well as clinical evaluations and neuropsychological tests. The determinants of the QoL were analysed by multiple stepwise regression analysis. Results: QoL was more impaired across the three groups (PD-NC < PD-MCI < PDD). The Unified Parkinson’s Disease Rating Scale part III (UPDRS-III) score, Geriatric Depression Rating Scale (GDS) score and daily levodopa equivalent dose (LED) were independent variables of PDQ-39 in PD-NC patients. The GDS score, disease duration, UPDRS-III score, Epworth Sleepiness Score (ESS) and sex were independent variables of PDQ-39 in PD-MCI patients. The GDS score and disease duration were independent variables of PDQ-39 in PDD patients. Conclusion: The determinants of QoL in PD-NC, PD-MCI and PDD patients were heterogeneous. Motor function was considered to be the most crucial determinant for QoL in PD-NC, while depression was indicated to be the most vital determinant for PD-MCI and PDD. For QoL improvement, clinicians might need to focus more on motor function in PD-NC patients and on depression in PD-MCI and PDD patients.